2019
DOI: 10.1108/bfj-01-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

The conceptualization of novel organic food products: a case study of Polish young consumers

Abstract: Purpose The purpose of this paper is to explore young consumers’ attitudes toward novel organic food products by analyzing their acceptability and perception. Design/methodology/approach A mixed method approach was applied to conceptualize (sensory profiling of organic bakery and confectionery products) and then to evaluate young consumer’s willingness to buy (consumer survey) innovative products: ten variants of rolls and ten variants of shortbread cookies made of certified raw materials originating from bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Moreover, results from Northern India show that the main reason for purchasing organic food is its perceived healthiness, while a lack of availability was identified as the main barrier, followed by high price, taste, and popularity (Paul and Rana, 2012). In contrast, a study conducted in Poland showed that the purchasing decision of young consumers is not strictly linked to concerns regarding health, nor is it linked to an awareness of the health-related attributes of these products (Radzyminska and Jakubowska, 2019). Vehapi and Dolicanin (2016) state that, even among interested individuals in Serbia, only a small percentage actually go shopping regularly, suggesting that there is a gap between consumer preferences and actual purchasing decisions regarding organic products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, results from Northern India show that the main reason for purchasing organic food is its perceived healthiness, while a lack of availability was identified as the main barrier, followed by high price, taste, and popularity (Paul and Rana, 2012). In contrast, a study conducted in Poland showed that the purchasing decision of young consumers is not strictly linked to concerns regarding health, nor is it linked to an awareness of the health-related attributes of these products (Radzyminska and Jakubowska, 2019). Vehapi and Dolicanin (2016) state that, even among interested individuals in Serbia, only a small percentage actually go shopping regularly, suggesting that there is a gap between consumer preferences and actual purchasing decisions regarding organic products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, in addition to the concept of "organic food", the concept of "organic agriculture" was identified, which reveals that organic food is associated with its mode of production and organic agriculture. While some definitions highlight dimensions such as "organic" or "natural" [17] and "environmentally sustainable" [18] or "future generations" [2], others emphasize the limited use of artificial chemicals in organic production [15,19]. Based on this, we can define organic food as: quality food products obtained according to the standards of organic agriculture, free of artificial chemicals, which promote the health of soils, ecosystems, and human beings, respecting future generations.…”
Section: Organic Foodmentioning
confidence: 99%
“…In Polish, young consumers had higher impact especially to innovation in food. They also more open to new product, that's why understanding young consumers had very good impact in companies operating on or in planning to enter the Polish food market (7). In India a research to know the acceptance level of young consumers on GMF (Genetically Modified Food) was conducted to analyse the potential of GMF market in India.…”
Section: Resultsmentioning
confidence: 99%